An intersectional human rights approach to prioritising access to COVID-19 vaccines. (24th February 2021) - Sekalala, Sharifah; Perehudoff, Katrina; Parker, Michael; Forman, Lisa; Rawson, Belinda; Smith, Maxwell
Abstract : We finally have a vaccine for the COVID-19 crisis. However, due to the limited numbers of the vaccine, states will have to consider how to prioritise groups who receive the vaccine. In this paper, we argue that the practical implementation of human rights law requires broader consideration of intersectional needs in society and the disproportionate impact that COVID-19 is having on population groups with pre-existing social and medical vulnerabilities. The existing frameworks/mechanisms and proposals for COVID-19 vaccine allocation have shortcomings from a human rights perspective that could be remedied by adopting an intersectional allocative approach. This necessitates that states allocate the first COVID-19 vaccines according to (1) infection risk and severity of pre-existing diseases; (2) social vulnerabilities; and (3) potential financial and social effects of ill health. In line with WHO's guidelines on universal health coverage, a COVID-19 vaccine allocation strategy that it is more consistent with international human rights law should ensure that vaccines are free at the point of service, give priority to the worst off and be allocated in a transparent, participatory and accountable prioritisation process.